Christian Values as the Foundation for Character Formation in Students in the Modern Era - Paparang, Stenly Reinal; Marjono, Marjono (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2024)
Character formation has become a central focus of education, particularly in the modern era marked by complex moral and social challenges. Christian values—such as love, integrity, responsibility, and respect for others—play a crucial role as the foundational basis for shaping students' character. This study aims to analyse the application of Christian values in character development and their impact on students’ personal, social, and spiritual lives. Employing a qualitative descriptive method, data were gathered through interviews, observation, and literature review. The findings reveal that the integration of Christian values in education—through moral-based curricula, the example set by teachers, and the presence of Christian communities—contributes significantly to the formation of students who are ethical, responsible, and possess integrity. Furthermore, these values empower students to act as agents of change within society. This study affirms the importance of value-based Christian education in cultivating morally grounded individuals who remain relevant in navigating the complexities of the modern era.